Comparison of the Heat Transfer Efficiency of Selected Counterflow Air-to-Air Heat Exchangers Under Unbalanced Flow Conditions - Kazimierz Kaminski; Pawel Znaczko; Ewa Kardas-Cinal; Norbert Chamier-Gliszczynski; Krzysztof Koscielny; Krzysztof Cur (Energies)
This study investigates the thermal performance of various counterflow air-to-air heat exchangers under unbalanced flow conditions, aiming to enhance the efficiency of heat recovery systems. Mechanical ventilation with heat recovery is critical in energy-efficient buildings to reduce heat loss, which can reach up to 60% in air exchange processes. This research focuses on the effects of flow imbalance on the heat transfer efficiency of three specific heat exchangers: two commercially available models (Recair Sensitive RS160 and Core ERV366) and a custom 3D-printed prototype (GV PROTO). Experimental tests measured temperature efficiency under both balanced and unbalanced flow conditions, with results indicating that flow imbalance significantly impacts thermal efficiency. Among the exchangers, the RS160 displayed the highest temperature efficiency, maintaining performance better than the others as flow rates increased. The results of the study show that even small differences in the thermal efficiency of different heat exchangers under balanced airflow conditions transform into significant differences under unbalanced conditions. These findings contribute to a better understanding of how real-world ventilation imbalances affect heat exchanger performance, offering insights to optimize energy efficiency in ventilation systems.